The Shift in Juozas Tumas-Vaižgantas’s Written Language: Approach to Standard Language - Venckienė , Jurgita (Colloquia, 2020)
Early noticing that there was a standard written Lithuanian language, Juozas Tumas-Vaižgantas tried to use it when speaking. By the late 19th century, there were no major discussions about which dialect to choose for the standard Lithuanian language. The South-Western Aukštaitian dialect was chosen, therefore Tumas had to avoid using his native Eastern Aukštaitian dialect. The aim of this article is to analyze Tumas’ written language and answer questions: how his written language had shifted and why and what his relationship with the emerging standard language was. In the late 19th century, two directions for the standard written Lithuanian language presented themselves. The first was represented by Catholic clergy and the second by the laity. The representatives of the first direction relied on the model of Kazimieras Jaunius’ language. The latter followed the language of the newspaper Varpas and Jonas Jablonskis. In the last decade of the 19th century, Tumas, then a student of the Samogitian (Telšiai) Seminary in Kaunas, relied on the language model of Catholic clergy. Tumas’ epistolary legacy shows that he also contemplated the language model of laity, considering which option was more rational. Jablonskis’s book on the Lithuanian grammar (1901) caused the shift in Tumas’s approach towards the language. Probably realizing that Catholic clergy had no intention of acknowledging Jablonskis’s authority, in the early 20th century, he began to rely on the suggestions of the priest Povilas Januševičius. However very soon, Tumas, seeing that the language model of laity was finally gaining ground in the press, had rejected Januševičius’s suggestions.